LRRK2 at the Interface Between Peripheral and Central Immune Function in Parkinson’s - Wallings, Rebecca L.; Herrick, Mary K.; Tansey, Malú Gámez (Frontiers in Neuroscience, 2020)
It is becoming increasingly accepted that there is an interplay between the peripheral immune response and neuroinflammation in the pathophysiology of Parkinson’s disease (PD). Mutations in the leucine-rich-repeat kinase 2 (LRRK2) gene are associated with familial and sporadic cases of PD but are also found in immune-related disorders, such as inflammatory bowel disease (IBD) and leprosy. Furthermore, LRRK2 has been associated with bacterial infections such as Mycobacterium tuberculosis and Salmonella typhimurium. Recent evidence suggests a role of LRRK2 in the regulation of the immune system and modulation of inflammatory responses, at a systemic level, with LRRK2 functionally implicated in both the immune system of the central nervous system (CNS) and the periphery. It has therefore been suggested that peripheral immune signaling may play an important role in the regulation of neurodegeneration in LRRK2 as well as non-LRRK2-associated PD. This review will discuss the current evidence for this hypothesis and will provide compelling rationale for placing LRRK2 at the interface between peripheral immune responses and neuroinflammation.